Harnessing silica nanoparticles grafted with ascorbic acid to alleviate oxidative stress and impaired brain activity in rats - Essia Hamdi; Slah Hidouri; Ana-Belén Muniz-Gonzalez; Marwa Kechnebbou; Salem Amara (Nano TransMed)
The brain has natural antioxidant defense systems, functioning through enzymes such as superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase, which neutralize reactive oxygen species (ROS). Once these defense systems are overwhelmed by poisoning, oxidative damage can occur in the brain. In this study, hydrogen peroxide (H2O2) was used to induce oxidative stress. Ascorbic acid grafted to silica nanoparticles (SiO2-NPs@AA) was used as a therapeutic strategy aimed to reduce ROS levels and enhancing antioxidant defenses. The SiO2-NPs@AA were synthesized and characterized, showing efficient functionalization with ascorbic acid. The in-vitro, antioxidant assays revealed that SiO2-NPs@AA exhibited significant radical scavenging activity (DPPH and hydroxyl radicals) and high iron-chelating ability with enhanced stability compared to free ascorbic acid. Moreover, the in-vivo study demonstrated that SiO2-NPs@AA mitigated H2O2-induced effects in key enzymes, including superoxide dismutase, catalase, glutathione (GSH), and restore acetylcholinesterase (AChE) levels. Notably, malondialdehyde (MDA) levels, a marker of lipid peroxidation, were significantly reestablished in the frontal cortex and hippocampus following SiO2-NPs@AA. Overall, the study revealed that SiO2-NPs@AA corrected effectively nitric oxide (NO) and monoamine oxidase activities, which confirm their role to preserve neuronal function and mitigate neurotoxicity.